(untitled)
This paper is devoted to studying direct and converse approximation theorems of the generalized Bernstein operators C_n(f,s_n,x) via so-called unified modulusω_φ^λ ^2(f,t), 0≤λ≤1. We obtain main results as follows ω_φ^λ ^2(f,t)=O(t^α)|C_n(f,s_n,x)-f(x)|=O((n^-12 δ_n^1-λ(x))^α),where δ_n^2(x)={φ^2(x),1/n} and 0, number=2, journal=Analysis in Theory and Applications, year=2014, month=Jun., pages=205–213